A colorimetric and fluorometric molecular system for discriminative detection of palladium acetate and CO cell imaging. (January 2023) - Fang, Xinkuo; Zhang, Yudi; Li, Mengfan; Zhang, Zehua; Qi, Yanyu; Zhang, Xiaobo; Zhang, Xuhong; Liu, Yun; Li, Jianwen; Yu, Haitao
Abstract: A novel fluorophore (NAP-PMA ) has been constructed through appending 2-pyridinemethanamine to naphthalimide. The air and moisture stable fluorophore were adopted as a colorimetric and fluorometric probe for palladium cation, revealing simultaneously good selectivity, high sensitivity and low detection limit (22.5 nM). Moreover, NAP-PMA not only exhibited a visible naked-eye color change from yellowish green to pink, but also displayed highly selective recognition to palladium acetate. In addition, NAP-PMA could be used as paper strips to quantitatively detect Pd 2+ in water. Surprisingly, the developed sensing platform NAP-PMA-Pd is capable of detecting CO in living cells by "turn on" mode with high selectivity and stability, providing a potential real-time monitor for CO-involved reactions in biological systems. Graphical abstract: A colorimetric and fluorometric naphthalimide-based probe, paper strips for palladium detection and CO cell imaging is reported. Image 1 Highlights: A colorimetric and fluorometric probe was constructed through appending 2-pyridinemethanamine to naphthalimide. It can realize visual and fluorescence recognition specific for palladium acetate. The probe exhibited record low detection limit as 22.5 nM together with good selectivity. Paper strips detection of palladium cations in aqueous media was realized. A sensing platform was exhibited for imaging of CO in living cells.